2007
DOI: 10.1103/physrevlett.99.036806
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Control of Interacting Electrons in Quantum Dots via Navigation in the Energy Spectrum

Abstract: Quantum control of the wave function of two interacting electrons confined in quasi-onedimensional double-well semiconductor structures is demonstrated. The control strategies are based on the knowledge of the energy spectrum as a function of an external uniform electric field. When two low-lying levels have avoided crossings our system behaves dynamically to a large extent as a two-level system. This characteristic is exploited to implement coherent control strategies based on slow (adiabatic passage) and rap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 18 publications
1
59
0
Order By: Relevance
“…This situation is of interest in a wide variety of quantum mechanical systems, such as molecular dipoles interacting with electric fields [33,34], ultracold atoms in optical lattices [35], Rydberg atoms [36] and superconducting qubits [37]. Using this particular interaction between the states of the system, we generate initial guesses for the control protocols using piecewise-constant functions derived from previous studies [38,39]. In a recent work, we studied the QSL time for these protocols by using QOC, and showed that the calculated QSL time is in general smaller than the sum of the optimal times for each avoided crossing [40].…”
Section: Introductionmentioning
confidence: 99%
“…This situation is of interest in a wide variety of quantum mechanical systems, such as molecular dipoles interacting with electric fields [33,34], ultracold atoms in optical lattices [35], Rydberg atoms [36] and superconducting qubits [37]. Using this particular interaction between the states of the system, we generate initial guesses for the control protocols using piecewise-constant functions derived from previous studies [38,39]. In a recent work, we studied the QSL time for these protocols by using QOC, and showed that the calculated QSL time is in general smaller than the sum of the optimal times for each avoided crossing [40].…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal Letter of Grossmann et al [8] a number of theoretical and experimental works have addressed the issue of controlling the localization of an electron state in a double well potential [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. These various control strategies include the use of analytically wellestablished phenomena like the paradigmatic LandauZener (LZ) transition [12][13][14], Landau-Zener-Stückelberg interferometry [15,16], the composite pulse (CP) protocol and several other two-level control strategies [12,[24][25][26][27], and OCT [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These various control strategies include the use of analytically wellestablished phenomena like the paradigmatic LandauZener (LZ) transition [12][13][14], Landau-Zener-Stückelberg interferometry [15,16], the composite pulse (CP) protocol and several other two-level control strategies [12,[24][25][26][27], and OCT [18][19][20][21][22][23]. For the experimental control strategies, as can be seen in [10,[15][16][17], the first stage is the measurement of the charge stability diagram (CSD).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been an increasing interest in controlling quantum phenomena in molecular systems and nanodevices [8,9,10,11,12,13,14,15], due to the possibility to modify the wave function of the system through the appropriate tailoring of external fields such as laser pulses. Coherent quantum control of electrons in quantum dots exposed to electromagnetic radiation is of great interest in many technological applications from charge transport devices to quantum information [16,17,18].…”
Section: Introductionmentioning
confidence: 99%